Innovative Technologies in Pedagogical Education - Tillyashaykhova M. A. (International Journal on Integrated Education, 2022)
This paper examines modern approaches to learning based on Internet technologies, presents the main factors that determine the need for the use of distance learning technology in the education system, shows the advantages and disadvantages of distance education as an innovative form of learning. The author considers both positive and negative aspects of distance learning and focuses on certain issues of the criteria for evaluating the effectiveness of distance education. There are two types of factors for the use of distance learning in the education system: external and internal factors.